Added Value of Long-Term Cytokine Release Assays to Detect Mycobacterium tuberculosis Infection in HIV-Infected Subjects in Uganda. (1st July 2016) - Dirix, Violette; Schepers, Kinda; Massinga-Loembe, Marguerite; Worodria, William; Colebunders, Robert; Singh, Mahavir; Locht, Camille; Kestens, Luc; Mascart, Françoise
Abstract : Objectives: To investigate whether mycobacterial antigen–induced cytokine secretions are helpful in detecting Mycobacterium tuberculosis ( Mtb ) infection in a cohort of HIV-infected patients living in a country with a high burden of Mtb and HIV infections, and to determine their predictive value for the development of tuberculosis (TB)-associated immune reconstitution inflammatory syndrome. Design: A total of 352 HIV-infected patients (186 with active TB) were prospectively enrolled when initiating antiretroviral therapy (ART). Sequential blood samples were collected during the first 6 months of ART. Eighty-three HIV-uninfected subjects (39 with active TB) were enrolled as controls. Methods: The concentrations of 13 cytokines were measured in supernatants from blood mononuclear cells in vitro stimulated with purified protein derivative (PPD), heparin-binding hemagglutinin (HBHA) or early secreted antigen-6 (ESAT-6) and culture filtrate protein-10 (CFP-10), and results were compared with those of tuberculin skin tests (TST). Results: The best detection of Mtb infection was achieved by ESAT-6/CFP-10–induced interferon-γ concentrations, but results were often negative for patients with CD4 + T-cell counts <50 per cubic millimeters. Patients with active TB were identified by high ESAT-6/CFP-10–induced interleukin-6. Conversions of interferon-γ-release assays (IGRA) and TST occurred under ART, and combined TB and antiretroviral treatments of coinfected patients resulted in a decrease of ESAT-6/CFP-10–induced and an increase of HBHA-induced interferon-γ responses. No Mtb antigen–induced cytokines allowed us to predict TB–immune reconstitution inflammatory syndrome or ART-associated TB. Conclusions: In Uganda, ESAT-6/CFP-10–IGRA is better in detecting Mtb infection than TST and, when combined with an HBHA–IGRA, could help to evaluate anti-TB treatment success. Abstract : Supplemental Digital Content is Available in the Text.